Transnationalizing the 'Moral neoliberal'? Private aid initiatives in Cambodia. (2nd January 2020) - Fechter, Anne-Meike
ABSTRACT: Within South East Asia, informal, non-state development actors have become more prominent. The case of small-scale, private aid activities in Cambodia offers the opportunity to reflect on how state frameworks and interventions matter for such projects. Typically, theories of how a state encourages its citizens' pro-social behaviour while retracting is own commitments, view this within a single nation state. Citizen aid in Cambodia, however, is often characterised by collaborations between national and international peers, and relies, to some extent, on resource flows along those networks. It encourages us to think through such approaches transnationally. This means broadening the analytical framework of the 'moral neoliberal' (Muehlebach 2012, The Moral Neoliberal: Welfare and Citizenship in Italy. Chicago, IL: University of Chicago Press) to account for the fact that activities of thus-responsibilised citizens expand beyond the confines of their nation state. In the Cambodian case, a lack of public service provision, combined with a hitherto loosely regulated third sector, have created conditions where such initiatives have proliferated. The case of private aid thus challenges the scope of 'moral neoliberal', as conceived within the framework of a nation state, as it leaves out of sight those 'ethical citizens' who are active transnationally.